Assessment of muscle function deterioration in aging populations: Insights from the load-velocity relationship during the loaded sit-to-stand test - Daniel Jiménez-Lupión; Ignacio Chirosa-Ríos; Rodrigo Lizama-Pérez; Luis Chirosa-Ríos; Daniel Jerez-Mayorga (Experimental Gerontology)
Muscle power is a better indicator of musculoskeletal health and functional capacity than muscle strength. The Load-Velocity (L-V) relationship provides a method for assessing muscle function during dynamic multi-joint movements, making it valuable for identifying age-related neuromuscular decline. This study aimed to examine the relationship between variables derived from the L-V relationship (L0, V0, and Aline) obtained during the loaded sit-to-stand test and various muscle performance indices, including knee extension peak force (KEPF) and various muscle quality indices (MQI).A total of 113 participants (49 middle-aged adults and 64 older adults; age = 61 ± 9.92 years) performed the loaded 5-Sit-To-Stand using Functional Electromechanical Dynamometry. L-V variables were calculated, and their relationships with indicators of muscle performance and quality were analyzed. The impact of age on these variables was also evaluated. The results showed a high positive correlation between Aline and KEPF, MQIEquation1, MQIEquation2 and MQIEquation3 (rs = 0.56–0.59, p ≤0.001–0.01), and between V0 and KEFP (rs = 0.51, p < 0.001). Older adults exhibited significantly lower L0 compared to middle-aged adults (76.86 ± 29.74 kg vs. 94.62 ± 35.69 kg, p = 0.007), as well as lower V0 (0.92 ± 0.28 m·s−1 vs. 1.22 ± 0.19 m·s−1, p < 0.001) and Aline values (35.39 ± 18.95 kg·m·s−1 vs. 57.75 ± 23.84 kg·m·s−1, p < 0.001). These findings suggest that L-V variables are valuable indicators for assessing muscle function deterioration and guiding training interventions, providing a more comprehensive and sensitive assessment of muscle quality and functional status in aging populations.